2019
DOI: 10.1080/21691401.2019.1609008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of miR-148b inhibiting cell proliferation and migration of Schwann cells by regulating CALR

Abstract: The aim of this study is to investigate the effect of miR-148b on cell proliferation and migration of Schwann cells and explore its mechanism. The miR-148b group, miR-con group and the anti-miR-148b group, anti-miR-con group, si-con group, si-CALR group, Ctrl group, CALR group were transfected into Schwann cells by liposome method; the expression of miR-148b was detected by qRT-PCR; the cell viability was detected by MTT assay; the migration of cells was detected by Transwell method; WB assay was used to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Previous study has indicated numerous methods that could promote the proliferation and migration of SCs [35][36][37] . However, these methods frequently involve in complex, di cult to be popularized, and what is more, these factors cannot enhance SC proliferation in the early stage by one hand and further promote SC migration in the late stage by the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has indicated numerous methods that could promote the proliferation and migration of SCs [35][36][37] . However, these methods frequently involve in complex, di cult to be popularized, and what is more, these factors cannot enhance SC proliferation in the early stage by one hand and further promote SC migration in the late stage by the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has indicated numerous methods that could promote the proliferation and migration of SCs [35][36][37]. However, these methods frequently involve in complex, difficult to be popularized, and what is more, these factors cannot enhance SC proliferation in the early stage by one hand and further promote SC migration in the late stage by the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a possible approach for the treatment of PNI. In addition, miR-34a and miR-148b overexpression evidently inhibited the proliferation and migration of SCs by targeting contactin-2 and calreticulin, respectively 60 , 61 . At the same time, a large number of miRNAs have been shown to promote the proliferation and migration of SCs.…”
Section: Non-coding Rnas In Peripheral Nerve Regenerationmentioning
confidence: 97%